Metode PCI dan Alternatif Perbaikan pada Kerusakan Ruas Jalan Urip Sumoharjo Bandar Lampung - Pujianto, Tri; Misdalena, Felly; Zain, Alfath (Universitas Batanghari Jambi, 2025)
Roads are very important transportation infrastructure in traffic flow. When there is a road section that is damaged, it will have a significant impact on traffic flow. Roads can be analyzed to determine the cause of the damage and repair alternatives. This study aims to determine the types of damage and road pavement conditions so that they can be determined how to repair them. The method used in this study is the PCI (Pavement Condition Index) method. Initial research on the condition of the road surface is to conduct a survey by observing and analyzing the road based on the types of damage to be used as a basis for carrying out road maintenance and repairs. To determine and group the types and levels of pavement damage, and determine the value of the pavement condition by finding the PCI (Pavement Condition Index) value and repair efforts. The results of damage to the Urip Sumoharjo road section, Bandar Lampung are marked with STA 0 + 000 - 3 + 000. The PCI value on the road section is 65.3% with good conditions based on the rating. The types of maintenance carried out to improve the level of road service according to the highway regulations on this section are asphalt coating, patching, and leveling.